Procalcitonin: Promising biomarker to detect sepsis in burns – A prospective study - H R. Naveen Kumar; Elvino Barreto; M Kingsly Paul; Ashish Kumar Gupta (Indian Journal of Burns, 2018)
Background: Sepsis-3 guidelines published in the Journal of American Medical Association is thought to be a pathbreaking effort in the diagnosis of sepsis,[1],[2],[3],[4] but it has limitations with respect to burns population.[5] On the other hand, the American Burn Association (ABA) 2007 guideline[6] for sepsis in burn patients is noted for low specificity rate. However, an independent biomarker procalcitonin (PCT) could augment clinical findings and improve sepsis predictability rate in burn patients. This study is the first attempt to assess diagnostic validity of PCT in Indian population and to highlight its role in diagnosing sepsis in burns despite newer sepsis-3 guidelines. Materials and Methods: This prospective study involved 33 consecutive thermal burn patients with 66 samples estimated for PCT. Samples were sent at each suspected episode of sepsis based on ABA guidelines. Baseline PCT estimation was done when the patient did not have sepsis. The positive blood or tissue culture was taken as a reference standard. The sample was divided into sepsis and nonsepsis group. All the parameters were documented on the graphical sheet which was interpreted by an independent analyzer. The sensitivity and specificity of each coordinate were plotted on receiver operating characteristic curve to identify the predictive ability of the test. Results: The sensitivity and specificity of the test was 94.7% and 85.7%, respectively. The cutoff value to diagnose sepsis in burn patients was 3.5 ng/ml with an area under the curve of 0.974 at 95% confidence interval. Conclusion: Good correlation between documented sepsis and elevated PCT levels makes PCT a promising biomarker in burns population.